2018
DOI: 10.1093/jnen/nly068
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Infiltration in the Saccular Intracranial Aneurysm Wall as a Response to Locally Lysed Erythrocytes That Promote Degeneration

Abstract: Saccular intracranial aneurysm (sIA) rupture is often fatal. Rupture-prone sIA walls are infiltrated by macrophages expressing hemoglobin-receptor CD163, suggesting a role for erythrocyte lysis in the degenerative remodeling predisposing to rupture. We therefore studied erythrocyte remnants in 16 unruptured and 20 ruptured sIA walls using histology and immunohistochemistry. Glycophorin A (GPA), an erythrocyte membrane protein, was present in 34/36 (94%) sIA walls and correlated with loss of αSMA+ cells, reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Besides these five genes, nine other transcripts ( CD163, TGS1, CYP26B1, ADTRP, OCLN, OLAH , C1QL1, FCRL5, and IGSF23 ) in the 26-transcript classifier reflect complex inflammatory processes, albeit not specifically attributed to neutrophil activation. For example, CD163 , which is abundant in the walls of IAs (but typically associated with macrophages [85, 86]), has been shown to be increased in neutrophils during sepsis [87] and thus could be contributing to vascular inflammation in IA. Expression differences of other transcripts, like TGS1 and CYP26B1 (that are differentially expressed in tuberculosis [88] and juvenile idiopathic arthritis [12], respectively) could be related to neutrophil responses to intravascular perturbations during IA.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these five genes, nine other transcripts ( CD163, TGS1, CYP26B1, ADTRP, OCLN, OLAH , C1QL1, FCRL5, and IGSF23 ) in the 26-transcript classifier reflect complex inflammatory processes, albeit not specifically attributed to neutrophil activation. For example, CD163 , which is abundant in the walls of IAs (but typically associated with macrophages [85, 86]), has been shown to be increased in neutrophils during sepsis [87] and thus could be contributing to vascular inflammation in IA. Expression differences of other transcripts, like TGS1 and CYP26B1 (that are differentially expressed in tuberculosis [88] and juvenile idiopathic arthritis [12], respectively) could be related to neutrophil responses to intravascular perturbations during IA.…”
Section: Discussionmentioning
confidence: 99%
“…Then the results of ROC curves showed that CD163, FCEREG, FPR1, ITGAM, NLRC4, PDG and TYROBP were potential circulating markers for predicting RIA. Among them, CD163 is a scavenger receptor for hemoglobin-haptoglobin complex phagocytosis [38], it is highly expressed in degenerated and ruptured IA walls [39]. The upregulation of FPR1 can induce the synthesis of neutrophils mediated by Mac-1 through fpr related Gi protein and b-arrestin signalling pathway, thus aggravating the development of abdominal aortic anerysm (AAA) [40], which suggest it may also participate in the development of IA.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Froesen and colleagues demonstrated differences in CD68+ and CD163+ macrophages in human ruptured and unruptured ICAs (29). Intriguingly, CD68+ and CD163+ (hemoglobin-haptoglobin scavenger receptor) macrophages, mostly HLA-DR-, co-localize with glycophorin A (a component of the erythrocyte membrane) and infiltrate ICAs as a response to a luminal thrombus trapped and lysed erythrocytes, and may promote degenerative arterial wall remodeling (46). In a mouse model of ICAs, M1 (F4/80+ iNOS+) dominate over M2 (F4/80+ Arg1+) during aneurysm development (47).…”
Section: Macrophage Polarization and Intracranial Aneurysmsmentioning
confidence: 99%